KAJIAN HIDROGEOLOGI UNTUK IDENTIFIKASI ZONA POTENSI SUMBER AIR BERBASIS PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS (SIG) DI WILAYAH KECAMATAN CIPATAT, KABUPATEN BANDUNG BARAT, JAWA BARAT - Adang Saputra; Ade Djumarma; Dadan Wildan; Murni Sulastri; Syahadun . (Universitas Negeri Padang, 2023)
Groundwater is the water contained in bedrock or regolith, it can also be said to flow naturally to the surface of the soil through jets or seepage. Groundwater has an important role especially for human needs. The research area is administratively located in Cipatat District, West Bandung Regency. Geographically it is located at 6°46'4.84